Educational Values contained in the Short Story My love is far away in Komodo by Seno Gumira Ajidarma - Dwi Febtiani (Bulletin of Social Studies and Community Development, 2022)
Abstract: In this article, the author analyzes short stories with a hermeneutic study that is associated with certain educational values that already exist. This because the short story My love is far from the dragons has educational value that can be applied in teaching Indonesian. The method used in this study uses a qualitative descriptive method by explaining the background of the short story. The topic of this essay is My Love Is Far in Komodo as a text that really needs understanding and approval for writing. The urgent situation is responded to and resolved by using hermeneutics as the formal topic of the current investigation. This study shows the results that the educational character values contained in short story texts, namely: loyalty, sincerity, optimism, perseverance, sincerity, optimism, hard work, patience, compassion, and curiosity. These values are contextual and actual.Keywords: hermeneutic studies, short stories, values, education